الرقمنة ودورها في الوقاية من الفساد ومكافحته في مجال الصفقات العمومية - بن هنية، نجاة; خالد، يسمينه (جامعة الوادي University of El Oued, 2024)
لقد ساهمت الثورة الرقمية التي يشهدها العالم اليوم مساهمة كبيرة في منع ومكافحة الفساد, وتعد رقمنة الصفقات العمومية أهم خطوة لمكافحة الفساد ، حيث ساهمت في إدخال تطبيقات جديدة لتعزيز الشفافية ونزاهة الإجراءات ، مثل الخدمات الإلكترونية , الرقابة الإلكترونية , والتوقيع الإلكترونية ، والتي تعتبر آليات فعالة تم من خلال اعتماد تكنولوجيا المعلومات والاتصالات ، خاصة فيما يتعلق بتحقيق مبدأ المساواة بين المتعاملين الاقتصاديين ,وتساهم الرقمنة بشكل فعال في الوقاية من الفساد ومكافحته ,باعتبار أن وجودها يتزامن مع سرعة إتمام المعاملات ، ويزيد من دقة الأعمال ومستوى جودتها وانضباط الموظفين ، وتوفر الوقت والجهد والمال. كما تساهم الوسائل التكنولوجية الحديثة في تسهيل وكشف التجاوزات والانحرافات التي يقوم بها الموظف العمومي، والتي يمكن اكتشافها إلكترونيا دون الحاجة إلى تدخل بشري، The digital revolution that the world is witnessing today has made a significant contribution to preventing and combating corruption, and the digitization of public transactions is the most important step in combating corruption, as it has contributed to the introduction of new applications to enhance transparency and integrity of procedures, such as electronic services, electronic control, and electronic signature, which are considered effective mechanisms that have been implemented. Through the adoption of information and communications technology, especially with regard to achieving the principle of equality among economic operators, digitization contributes effectively to preventing and combating corruption, given that its presence coincides with the speed of completing transactions, increases the accuracy of business, its level of quality, and employee discipline, and saves time, effort, and money. Modern technological means also contribute to facilitating and detecting violations and deviations committed by public employees, which can be discovered electronically without the need for human intervention
ماستر اداري